Land Reform and Farm Restructuring in Transition Countries : The Experience of Bulgaria, Moldova, Azerbaijan, and Kazakhstan - Dudwick, Nora; Fock, Karin; Sedik, David (Washington, DC: World Bank, 2012)
This paper presents such a stocktaking of land reform and farm restructuring in four countries (Azerbaijan, Bulgaria, Kazakhstan, and Moldova) that have had particular difficulties with land reform, farm restructuring, farm performance, or rural poverty. It is organized by case studies, each of which is designed to analyze a central conundrum about land reform and farm restructuring in an individual country. Much of the information presented in this review derives from farm and household surveys conducted in each of the four countries during 2003 and 2004. The surveys were designed to provide information that would be comparable across countries. Surveys were supplemented by individual and focus group discussions.